PENGELOLAAN WAKAF UANG BERKEADILAN SOSIAL: PENGELOLAAN INVESTASI DAN MANFAAT WAKAF UANG MELALUI PEMBIAYAAN MIKRO OLEH BMT - Hilmi, Hasbullah (al-Rasῑkh: Jurnal Hukum Islam, 2024)
Empowering the poor can be achieved by expanding access to financial institutions and funding. This study explores a financing and business incubation model based on cash waqf through Baitul Mal wa Tamwil (BMT). The research begins with an analysis of cash waqf instruments, regulations, and their implementation in Indonesia, drawing insights from M.A. Mannan's Cash Waqf Certificate and Muhammad Yunus' Grameen Bank concept. BMT, as a unique mikrofinance institution in Indonesia, integrates sosial and economic functions within a single entity. The findings indicate that BMT is an ideal institution for managing cash waqf. Waqf funds are invested in mikro-business financing, with returns allocated for training and business development programs targeting the poor. By synergizing its sosial and economic roles, BMT serves as a strategic solution for sustainable, waqf-based economic empowerment.